1993
DOI: 10.1017/s0021859600076528
|View full text |Cite
|
Sign up to set email alerts
|

Soil inorganic-N and nitrate leaching on organic farms

Abstract: SUMMARYOn two organic farms, nitrate-N and ammonium-N in the surface layers of the soil of representative fields were recorded for 2 years. Nitrate-N was also determined in different soil layers down to 120 cm at the beginning, middle and end of two winters and at intervals after ploughing three fields, to seek evidence of leaching.Nitrate-N and ammonium-N were both consistently low in the surface layers of fields in ley. Nitrate-N accumulated in arable soils on some occasions when there was little or no crop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 4 publications
2
20
0
Order By: Relevance
“…Addiscott and Darby (1991) also observed a movement of N down the soil profile, depending on the drainage up to that date. Similar soil N profiles to ours were found by Kuhlman et al (1989) and Watson et al (1993) in winter wheat, with most N moved below 1 m. However, at harvest, deep roots of winter wheat had depleted most of this N, whereas large amounts of N were left after spring wheat. Other studies indicate similar results after spring wheat (Campbell 2006a, b), but when spring wheat crop was replaced by a autumn seeded rye crop, there was hardly any N leached (Campbell 2006b), supporting our findings with winter wheat.…”
Section: Soil N Depletionsupporting
confidence: 90%
See 2 more Smart Citations
“…Addiscott and Darby (1991) also observed a movement of N down the soil profile, depending on the drainage up to that date. Similar soil N profiles to ours were found by Kuhlman et al (1989) and Watson et al (1993) in winter wheat, with most N moved below 1 m. However, at harvest, deep roots of winter wheat had depleted most of this N, whereas large amounts of N were left after spring wheat. Other studies indicate similar results after spring wheat (Campbell 2006a, b), but when spring wheat crop was replaced by a autumn seeded rye crop, there was hardly any N leached (Campbell 2006b), supporting our findings with winter wheat.…”
Section: Soil N Depletionsupporting
confidence: 90%
“…Deep soil N depletion by catch crops during autumn and winter has previously been reported (ThorupKristensen 2006), but not much information about N content below 1 m is available for winter wheat. Often shallow soil samplings have been used in winter wheat studies (Baeckstöm et al 2006;Karlen et al 1996;Smith et al 1998;Watson et al 1993) assuming little activity of wheat roots below 1 m depth, and therefore, N below this depth is often considered lost. Our results show that this may lead to misleading conclusions.…”
Section: Soil N Depletionmentioning
confidence: 99%
See 1 more Smart Citation
“…The management practices are incorporated into regulations covering agriculture in Nitrate Sensitive Areas (NSAs) and management practice guidelines for Nitrate Vulnerable Zones (NVZs), where a combination of computer modelling and field sampling has shown that reductions in nitrate losses from agricultural land can be achieved (Lord, 1992;Lord et al, 1993). Nevertheless, relationships between leached nitrate and applied nitrogen, atmospheric inputs, and the production of nitrate from organic nitrogen in the soil under different land management systems are complex (Milford et al, 1993;Watson et al, 1993;Francis et al, 1995). Specific agricultural activities contribute substantially to losses of nitrate.…”
Section:  mentioning
confidence: 99%
“…Any estimates made are often based on nutrient budgets (e.g. Halberg et al, 1995;Dalgaard et al, 1998;Hansen et al, 2001), mineral N content in soil (Watson et al, 1993;Kristensen et al, 1994) or modelling (Johnsson et al, 2006) rather than direct measurements. In terms of leaching, the nutrient surpluses calculated in this way are simply indicators of the potential losses from the systems (Dalgaard et al, 1998) with no partition between different losses (e.g.…”
Section: Introductionmentioning
confidence: 99%